Turkey : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper examines the new private pension automatic enrollment provisions in Turkey. The newly enacted automatic enrollment provisions have several advantages relative to the current voluntary private pension system. However, they have several weaknesses that risk endangering the reform in the long term. The hybrid input-output is not complete without the establishment of a public procurement board and periodic auctioning of pension services. Employers are unlikely to be more skilled than individuals in choosing pension plans for their workers. The IMF staff advice is to complete the hybrid input-output model along the lines recommended by the World Bank by establishing a procurement board for pension services for undecided participants.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet